The Geopolitics of Central Bank Digital Currencies - Maria Demertzis; Josh Lipsky (Intereconomics, 2023)
Central bank digital currencies (CBDCs) are reshaping the financial landscape globally. Already implemented in ten countries, CBDCs offer digital payment solutions, particularly beneficial for regions with limited access to traditional banking systems that seek to promote financial inclusion. However, in more advanced financial systems, CBDCs may appear less compelling, with existing alternative digital payment methods already prevalent. Still, even these financial systems have incentives to consider the development of CBDCs and to explore how to reap the benefits of this new technology. This Forum features articles by the speakers at our recent event, organised jointly with Bruegel and the Atlantic Council. The authors define CBDCs, debate their pros and cons, examine the issues and prospects they represent, and share country-specific experiences with the development and roll-out of digital currencies.
Keywords: E58; F02; 330